Underwater Image Gathering by Utilizing Stationary and Movable Sensor Nodes: Towards Observation of Symbiosis System in the Coral Reef of Okinawa. (14th July 2014) - Kawabata, Kuniaki; Takemura, Fumiaki; Suzuki, Tsuyoshi; Sawai, Kei; Kuraya, Eisuke; Takahashi, Satoru; Yamashiro, Hideyuki; Isomura, Naoko; Xue, Jianru
Abstract : This paper describes the underwater data collection utilizing stationary sensor node and movable sensor node. We consider applying the system to investigate the conditions of marine ecosystem around the coral reef at Okinawa, Japan. The framework and fundamental design of our proposed underwater information gathering system under development are introduced. It is also reported the development of the prototypes of the sensory node and movable sensor node. Basic examinations utilizing such prototype at underwater environment are also described. This paper also describes experimental results of image gathering from via wireless local area network communication. Our future trials based on the current developmental situation are also discussed.